Analysis of autonomic function during natural defecation in patients with irritable bowel syndrome using real-time recording with a wearable device - Rieko Nakata; Fumio Tanaka; Noriaki Sugawara; Yuichi Kojima; Toshihisa Takeuchi; Masatsugu Shiba; Kazuhide Higuchi; Yasuhiro Fujiwara (PLoS ONE, 2022)
Background Autonomic dysfunction is a factor in irritable bowel syndrome (IBS). However, there are no reports of autonomic nervous system (ANS) activity during natural defecation in patients with IBS. We aimed to clarify the relationship between ANS activity and life events, such as defecation and abdominal symptoms, using real-time recording. Methods Six patients with IBS and 14 healthy controls were enrolled in this prospective multicenter study. ANS activity was recorded for 24 h using a T-shirt wearable device, and life events were recorded simultaneously in real time using a smartphone application software. Low frequency/high frequency (LF/HF) and HF calculated by power spectrum analysis were defined as activity indicators of the sympathetic and parasympathetic nerves, respectively. Results The means of LF/HF and HF in the period with positive symptoms were comparable between the groups; however, the sum of LF/HF, sum of ΔLF/HF, and the maximum variation in ΔLF/HF were significantly higher in the IBS group. In the IBS group, the sum of ΔLF/HF and LF/HF increased significantly from 2 min before defecation, and the sum of LF/HF remained significantly higher until 9 min after defecation. The sum of ΔLF/HF at 2 min before defecation was significantly positively correlated with the intensity of abdominal pain and diarrhea and constipation scores. In contrast, it was significantly negatively correlated with defecation satisfaction and health-related quality of life. Conclusions In patients with IBS, sympathetic nerve activity was activated 2 min before defecation, which was correlated with abdominal symptoms and lower QOL.